A4.7 T and B cells participate in bone repair by infiltrating the fracture callus in a two-wave fashion. (13th February 2015) - Serra, A; Könnecke, I; Khassawna, T El; Schlundt, C; Schell, H; Hauser, A; Ellinghaus, A; Volk, HD; Radbruch, A; Duda, GN; Schmidt-Bleek, K
Abstract : Background and objectives: Fracture healing is a regenerative process and is one of the two processes in the human body in which an organ is restored without scar tissue formation. The healing cascade initiates with a cycle of inflammation, cell migration, proliferation and differentiation. Immune cells invade the fracture site immediately upon bone damage and contribute to the initial phase of the healing process and appear to recruit accessory cells to the injury site. However, little is known about the role of the immune system in the later stages of fracture repair, in particular, whether lymphocytes participate in soft and hard callus formation. Materials and methods: In order to answer this question, we analysed femoral fracture healing in mice by confocal microscopy, flow cytometry and molecular biology. Results: Upon fracture, we could detect generalised increased frequencies of T cells in the bone marrow of injured mice which persisted throughout healing. By closely analysing the fractured bone, we found that surprisingly, after the initial inflammatory phase, when soft callus developed, T and B cells withdrew from the fracture site. Thereafter lymphocytes massively infiltrated the callus region (around day 14 after injury), during callus mineralisation. Interestingly, lymphocytes were not found within cartilaginous areas of the callus but only nearby newly forming bone. During healing, B cell numbers seemed to exceed those of T cells and B cells progressively underwent effector maturation associated with high OPG production capacity. During bone regeneration, both osteoblasts and osteoclasts were found to undergo direct cell-cell contact with lymphocytes. The latter were also found to secrete OPG in the callus and their appearance also correlated with a progressive increase in the ratio of OPG vs. RANKL gene expression during fracture repair. Conclusions: Our data strongly suggests a regulatory role of T and B cells not only in the initial phase of healing but specifically also in the later stages of fracture remodelling.